Global Positioning In Amitav Ghosh’S the Hungry Tide: Exploring Globalization and Ownership in Amitav Ghosh's The Hungry Tide (Journal of Advances and Scholarly Researches in Allied Education, 2012)
As we move towards the end of the first decade of thetwenty-first century and debates about globalization gather ever-increasingmomentum as part of the staple fare of academic discourse, not to mentioneveryday life, one of the dilemmas facing much Indian writing in Englishrelates to ownership. Who is writing,who is publishing their work and who are they publishing it for? For Indian andIndian-diaspora writers publishing their work in the West, the dynamics ofmetropolitan publishing seem to be encouraging an encounter with alterity, butthe terms of this encountrer are being brokered by Western-based, globalizedperceptions of the market.